South-Western Federal Taxation 2020: Comprehensive, 43rd Edition - David M. Maloney; William A. Raabe; James C. Young (Cengage Learning, 2019)
Master today's tax concepts and gain a thorough understanding of current tax legislation with Maloney/Raabe/Young/Nellen/Hoffman's SOUTH-WESTERN FEDERAL TAXATION 2020: COMPREHENSIVE VOLUME, 43E. This complete, understandable book provides today's most effective solution for understanding individual taxation, C corporations, taxes on financial statements and flow-through entities. Updated coverage details the latest tax legislation for both individual taxpayers and corporations, as of the time of publication, including tax reforms of 2018 and the Tax Cuts and Jobs Act of 2017. Engaging learning features, such as ""Big Picture"" examples, memorable tax scenarios and ""What If?"" case variations help clarify concepts. These features also strengthen critical-thinking, writing and online research skills that are key to your success as a tax practitioner. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.